Impact of Risk Budgeting on Enhancing the Projected Growth of the Hotel Industry under the Conditions of Enduring Uncertainty Related to the COVID-19 Pandemic. Case Study by Republic of Kazakhstan - YEMBERGENOV, Ruslan; MURATOVA, Diana Baltabayevna; POPP, Lyudmila; ARZAYEVA, Maiya; ABDYKULOVA, Karlygash (Journal of Environmental Management and Tourism, 2022)
The article considers the possibility of using a risk budgeting approach in forecasting the development of the hotel business in the Republic of Kazakhstan. This study aims at elaborating three budget scenarios for the sales of services provided by accommodations with due regard to the possible risks associated with COVID-19. To attain this end, the authors used a set of budget planning methods, including expert assessments, scenario analysis, and Monte Carlo simulation. The results obtained allow the authors to determine the ranges of probable values and the most probable indicators for the budget items of hotel enterprises in the Republic of Kazakhstan. At the same time, the resulting model does not assess the simultaneous impact of other risks that the hotel industry is exposed to. The authors of the article believe that the construction of multi-factor risk budgeting models for the hotel business is the subject of further scientific research.